Open Access Esophagogastroduodenoscopy. - Hassan, Riyadh M.; Kamal, Zuhair B.; Al Marzook, Tawfiq J.; Hussein, Wisam A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Open access gastroduodenoscopy allows general practitioners to request gastroduodenoscopy without prior referral to a specialist. Endoscopy of the upper gastrointestinal tract in experienced hands has definite advantages over conventional barium-meal examination.Patients and Methods: A total of 266 patients who were referred directly from general practitioner or a specialist attending for esophagogastroduodenoscopy (EGD) to the Endoscopy Unit At Al-Kindi Teaching Hospital from September- 2008 to Feb-2010 as an open access policy. Six inclusion criteria were used to include patients in our study group , while 136 patients had underwent EGD were referred from outpatient clinics of the hospital by specialist after screening and filtration were included in the study. Data were obtained from patients include chief complaint and duration and full history of present illness with special emphasis on age, gender, symptoms (abdominal pain, vomiting, loss of weight or appetite, hematemesis, melena, dysphagia), and history of present medications. EGD was done for all patients with gastroscope Pentax EG-2985K2.8.Results: Two hundred sixty six patients were included in the study and underwent EGD . One hundred thirty EGDs were done in this study as an open access EGD policy while 136 EGD were done for patients who were referred from outpatient clinics of the hospital. In open access EGD policy, 66.15% of patients were males and 33.85% patients were females. The most commonly affected age group which showed abnormal endoscopic findings were in the second decade of life (20-29 years) 22.31% of cases; the chief complaint was epigastric pain in 87.69% of patients. Normal EGD was found in 23.07% of patients while pathological lesions were seen in 76.93% of patients. Gastro esophageal reflux disease (GERD) was the most common condition encountered by EGD  (33.08%). While 136 patients referred from outpatient clinics of the hospital underwent EGD, 68.38% of patients were males and 31.62% of patients were females, most of the patients were in the third decade of life (28.67%), normal EGD was found in 44.12% of patients. Chronic active DU and GERD were the most common diagnoses 12.5%, 11.76% respectively.Conclusions: The clinical assessment and the strict application of the six inclusion criteria in open access EGD policy increase the yield of diagnosis of pathological lesions and decrease the number of unnecessary EGDs in our study.